2011
DOI: 10.1590/s1516-31802011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and cost estimate of treating pediatric adverse drug reactions in Lagos, Nigeria

Abstract: CONTEXT AND OBJECTIVES: Adverse drug reactions (ADRs) may cause prolonged hospital admissions with high treatment costs. The burden of ADRs in children has never been evaluated in Nigeria. The incidence of pediatric ADRs and the estimated cost of treatment over an 18-month period were determined in this study. DESIGN AND SETTING:Prospective observational study on children admitted to the pediatric wards of the Lagos State University Teaching Hospital (LASUTH) in Nigeria, between July 2006 and December 2007. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 41 publications
1
53
2
Order By: Relevance
“…Our proportion of serious ADRs considered preventable, i.e. 23%, is considerably lower than the findings in our adult serious ADR surveys, where 43 to 45% of ADRs were considered preventable [10,29], but is in keeping with proportions from Nigeria (20%) [21] and Ethiopia (33%) [22]. The most common reason why serious ADRs were considered preventable in this survey was an inappropriate choice of drug (15%), which was also the most common reason in our adult surveys [10,29] and one of the most common reasons (23%) cited in the 2012 systematic review [4].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our proportion of serious ADRs considered preventable, i.e. 23%, is considerably lower than the findings in our adult serious ADR surveys, where 43 to 45% of ADRs were considered preventable [10,29], but is in keeping with proportions from Nigeria (20%) [21] and Ethiopia (33%) [22]. The most common reason why serious ADRs were considered preventable in this survey was an inappropriate choice of drug (15%), which was also the most common reason in our adult surveys [10,29] and one of the most common reasons (23%) cited in the 2012 systematic review [4].…”
Section: Discussioncontrasting
confidence: 79%
“…However, our survey excluded admissions to the oncology ward, whereas the 2012 systematic review's figure is significantly influenced by two large surveys which found ADR-related admissions to oncology wards to be common [17,18]. Published subsequent to the 2012 systematic review [4], surveys from paediatric settings in sub-Saharan Africa suggested the proportion of admissions due to ADRs to be 5.7% (16/282) in Cape Town, South Africa [19], 4.7% (114/2433) in Eritrea [20], and 0.60% (12/2004) in Lagos, Nigeria [21]. A study from Jimma, Ethiopia, with paediatric adverse drug events as outcome (i.e., a slightly different outcome than ADRs), determined the proportion of admissions to be adverse drug event-related as 0.63% (4/634) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic use was related to a higher risk of ADRs emergence, as reported by Oshikoyay et al . 28 , and Martinez-Mir et al . 21 , who found that antibiotics were the most common cause of ADRs.…”
Section: Discussionmentioning
confidence: 97%
“…In children, ADRs surveillance and documentation is crucial to monitor the safe use of the medications used in this population since, compared to adults, children may have higher vulnerability for experiencing ADRs because: a) clinical trials carried out in these population are scarce [2,3]; b) unlicensed and off-label drugs are often prescribed [4]; c) there is the possibility of exposure to medications during prenatal stage and breastfeeding [5], d) children may react differently than adults to administered medications, which can be explained by changes in absorption, distribution, metabolism and excretion [6], and e) hospitalized pediatric patients can be administered more than 10 drugs during their stay [7,8]. In the pediatrics setting, ADRs generate a significant impact on morbidity, mortality [9][10][11] and costs [12,13]. Frequency in hospitalized children ranges from 1.5% to 18.1%, while in outpatients it ranges from 0.7% to 2.74%; in addition 0.2% to 5.8% result in hospitalization [14,15].…”
Section: Introductionmentioning
confidence: 99%